2012
DOI: 10.25103/jestr.054.06
|View full text |Cite
|
Sign up to set email alerts
|

On the Design of an Intelligent Battery Charge Controller for PV Panels

Abstract: The electricity generations of photo voltaic (PV) panels are strongly related with insolation and temperature. The insolation and temperature are not stable, since the electricity generations of the PV panels are not stable. In PV systems, insolation and temperature continuous vary. Therefore, the maximum power point tracking (MPPT) techniques are used to give the highest power to the loads/batteries. The MPPT process is performed with a power electronic circuit and it overcomes the problem of voltage mismatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The most important factor in increasing the efficiency of a PV system is designing an MPPT to extracting maximum power from the panel. In [26], a microcontroller, NIBB converter, a DC load, and lead-acid battery were integrated into a system to show that the selected converter can perform the MPPT technique. In this study, NIBB operates as a battery charger and can deliver maximum power from the panel to the DC bus.…”
Section: B Non-inverting Buck-boost Convertermentioning
confidence: 99%
“…The most important factor in increasing the efficiency of a PV system is designing an MPPT to extracting maximum power from the panel. In [26], a microcontroller, NIBB converter, a DC load, and lead-acid battery were integrated into a system to show that the selected converter can perform the MPPT technique. In this study, NIBB operates as a battery charger and can deliver maximum power from the panel to the DC bus.…”
Section: B Non-inverting Buck-boost Convertermentioning
confidence: 99%
“…Furthermore, Liu and Hsu adopt the particle swarm optimization (PSO) technique for a static synchronous compensator (STATCOM) in finding a suitable standard value of intelligent PI controller [14]. Ultimately, Çınar and Akarslan design an intelligent battery charger controller for PV panels due to the its various capabilities [15]. Hence, a PI controller is operated to control the farming load system, the battery charger system, and the system which can supply to grid-connected system.…”
Section: Introductionmentioning
confidence: 99%
“…not grid-connected) photovoltaic (PV) systems. So that, problem of surplus or reduction of the producing power can be solved [1]. Another purpose of using the batteries in the off-grid photovoltaic power system is to store the electrical energy produced by the PV panel during the sunshine period and restore it during night time, sunless periods and those of weak irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies have shown that the life time of the battery is degraded without using charge controller. Therefore, an optimal charge controller should be designed to prolong the battery's life time [1] [3].…”
Section: Introductionmentioning
confidence: 99%